護國神山、民主世界的ＭＶＰ與美麗之島福爾摩沙 : ２０２４年中華民國總統候選人以隱喻建構台灣國家認同之論述分析 - Heikkinen, Tuuli (My University, 2024)
隨著中華民國公民中自視「主要為台灣人」的人數迅速增加以及自視「主要為中國人」人數的縮小，台灣國家認同的概念正經歷著重大的變遷過程。同時，這一變遷的影響不僅限於台灣社會內，還將會影響海峽兩岸關係及全部印太地區的發展。然而，從語言學的角度來探索該現象仍存在空白。因此，本研究將探討 2024 年總統候選人如何運用結構性隱喻、實體隱喻及隱喻型符碼轉換以建構台灣國家認同論述。本文的研究問題包括：（一）三位總統候選人在其政治修辭中運用的隱喻與隱喻型符碼轉換是如何建構台灣國家認同論述的（二）三位總統候選人所建構的論述以及建構論述的手段之間有何異同（三）三位總統候選人所建構的論述及建構論述的手段與更廣泛的政治語境有何關聯？為了回答上述研究問題，本文借鑑 Lakoff 與 Johnson （1981） 的概念隱喻理論、 Drogosz （2008） 對隱喻類型的界定，以及 Wei （2003、2008）對台灣政治語境中的符碼轉換的研究。至於研究方法，本文採用了功能導向的論述分析法，即論述分析法的子類之一。本研究材料以 2024 年競選期間候選人的相關政見發言為主，其包括《台灣新聞》、《公視新聞網》、《自由電子時報》及《NN思咪達》的報導、總統候選人的個人YouTube頻道，以及個人志工在網路上分享的候選人演講逐字稿。本文發現，侯友宜與賴清德運用隱喻建構了屬於「中華民國主義」及「台灣公民主義」兩種國家認同論述的取向。柯文哲則結合了不同國家認同論述取向的特質來建構一種全新的台灣國家認同論述。另外，候選人所運用的隱喻表達了不同國家認同論述之間的對立，尤其是關於中華民國的地位及威脅國家存在因素的論述。同時，「新台灣人」論述的理念在所有候選人的論述中均可被觀察到，顯示出該論述在台灣政治論述中具有潛在的主導地位。此外，「島嶼認同」的特質也顯著地影響了諸位候選人的國家認同論述，儘管每一位候選人對這些特質的表達方式各有不同。本研究發現將有助於更廣泛地理解國家認同論述在多元文化與多元語言民主社會中的建構方式。此外，通過探討隱喻在民主台灣社會的運用，它也將有助於加深我們對隱喻在華人社會政治論述中所扮演的角色的認識。對於今後的研究，本文建議將論述分析法與統計方法相結合，通過探討廣泛的研究材料，對不同國家認同論述的對抗或主導論述做出有效的推斷。

The concept of Taiwanese national identity is undergoing a significant transformation process, with a steady increase in citizens of the Republic of China (Taiwan) identifying primarily as Taiwanese, while identification solely as Chinese has become marginal. Simultaneously, this transformation not only affects Taiwanese society but also shapes the development of cross-strait relations and the entire Indo-Pacific region. However, few studies have delved into the construction of Taiwanese national identity from a linguistic perspective. Thus, this paper aims to explore how structural metaphors, ontological metaphors and metaphorical code-switching are employed by the presidential candidates during the ROC 2024 Presidential Election to construct Taiwanese national identity discourse. The research paper aims to answer the following questions: (1) How do the three presidential candidates use metaphors and metaphorical code-switching in their political rhetoric to construct Taiwanese national identity discourse? (2) What are the similarities and differences created by the three candidates and the methods they use to create these discourses? (3) How do these discourses and their creation methods relate to the wider political and linguistic context? To answer these questions, this paper draws on Lakoff and Johnson’s (1981) Conceptual Metaphor Theory, Drogosz’s (2008) categorization of metaphor types, and Wei’s (2003, 2008) research on code-switching in the Taiwanese political context. As for the research methodology, this paper utilizes the functionally oriented discourse analysis, which is one of the subtypes of the discourse analysis method. The research data consists of televised electoral speeches made by the candidates, including news materials from TTV News, PTS News, Liberty Times and nnyy.tw, the candidates’ personal YouTube Channels, as well as speech transcripts shared online by individual volunteers. The study finds that the metaphors used by Hou Yu-ih and Lai Ching-te construct discourses oriented towards ROC Chinese nationalism and civic Taiwanese nationalism. Respectively, Ko Wen-je combines traits of different national identity orientations to construct a new kind of Taiwanese national identity discourse. The metaphors used by the candidates express confrontation between different national identity discourses, particularly concerning the position of the Republic of China and the elements threatening national existence. Meanwhile, the New Taiwanese discourse is observable in all candidates’ discourses, suggesting its potential hegemony. Furthermore, the characteristics of “islandness” evidently shape the candidates’ discourses, albeit expressed differently by each candidate. These findings aim to enhance understanding of Taiwanese national identity discourse and its construction within the electoral context. Additionally, this study seeks to contribute to a broader comprehension of how national identity is constructed in multicultural and multilingual democratic societies, as well as to expand understanding of the role of metaphors in political discourse in societies possessing elements from the Chinese cultural sphere. For future research, this paper suggests combining discourse analysis with statistical methods to make valid inferences about the confrontation or hegemony of different national identity discourses through the exploration of extensive research materials.
Keywords: 國家認同、論述、政治修辭、隱喻 national identity, discourse, political rhetoric, metaphor